The particulars of Peter : dance lessons, DNA tests, and other excuses to hang out with my perfect dog - Conaboy, Kelly (Grand Central Publishing, 2020)
Conaboy met Peter in the spring of 2017, when he came to her first as a foster. The rescue needed someone free of the sort of responsibilities that would force her to regularly leave the house for either work or socializing, and a writer was the natural choice. This joyful book is the culmination of Conaboy's desire to dedicate months to learning more about Peter. From learning about Peter's DNA, to seeing if dogs can sense the presence of ghosts, this is a smart, entertaining respite from the harsh world of humans into the funny little world of dogs. -- adapted from jacket